Doing activism: understanding activists’ identity, practice, and the LGBT movement in Yunnan, China - Yifu Liu; Sai Tang (Frontiers in Psychology, 2025)
As social movement theory evolved, activist identity gained attention for playing a crucial role in the development and outcomes of social movements. This study investigates the influence of “activist identity” on the actions and behaviors of LGBT movement activists in Yunnan, China and how these contribute to the unique characteristics of the local LGBT movement. It is a qualitative study based on in-depth interviews with 20 LGBT grassroots activists in Yunnan, China. The researchers draw a parallel between West and Zimmerman’s classic theorization of “doing gender” and the findings of this study. Building upon their original conceptualization and incorporating insights from identity theory and dramaturgy, the current study narratively analyzes how the identity of the front-line activists is influenced and shaped through their everyday action. The researchers term this as “doing activism” which connotes activism as a routine accomplishment embedded in everyday interactions that allows individuals to reaffirm their self-identity as an activist and reinforce the recognition of their belonging to the LGBT movement by “others”. The “doing of activism” is both informed by and in turn creates the idea of an “ideal activist”, a status to be achieved through everyday effort. Further, the researchers argue that “doing activism” emphasizes the importance of action as a manifestation of identity and engagement in the LGBT movement. Practical outcomes in the context of the LGBT movement in Yunnan and implications for social movement field are also discussed.